Biological and management design for sustainable wetland rice farming in Siak District, Riau, Indonesia - RACHMIWATI YUSUF; INDRA FUADI; USMAN M. TANG; RAHMAN KARNILA; Usman Pato (Society for Indonesian Biodiversity, 2021)
Abstract. Yusuf RA, Tank UM, Karnila R, Pato U. 2021. Biological and management design for sustainable wetland rice farming in Siak District, Riau, Indonesia. Biodiversitas 22: 2803-2814. This study aimed to develop a management design for sustainable wetland rice farming to promote food security in Siak District, Riau Province. This study was conducted through survey research wherein primary and secondary data were used. In the sustainability analysis, the Rapfish method was used which is based on eight attributes that are a combination of key factors in the sustainability analysis and stakeholder needs analysis. Results showed that the management design that can be implemented to improve the sustainability of rice farming involves preventing the continuous paddy field conversion and thus promote their preservation, improving the farmers’ knowledge and skills to create superior human resources, and strengthening agribusiness-based farmer institutions to improve farmers’ welfare. The multidimensional sustainability value obtained in three scenarios was within the 50–75% range, indicating a fairly sustainable status. For this reason, it is recommended to apply scenario 1 wherein sustainability can be increased at low costs and within a relatively short time